Violence in dating relationships: Validation of the Dominating and Jealous Tactics Scale in Spanish youth - Muñoz-Rivas, Marina J.; Redondo, Natalia; Zamarrón, Dolores; González, María Pilar (Anales de Psicología / Annals of Psychology, 2018)
The Dominant and Jealous Tactics Scale (Kasian & Painter, 1992) is one of the most extensively used instruments to measure dominance and jealousy in dating relationships of young adults and adolescents. The goal of this study is to analyze the psychometric properties of this scale and validate its adequacy for young Spanish population. the sample was made up of 8105 youths from the Region of Madrid, aged between 14 and 26 years. Results of the confirmatory factor analysis indicate two correlated factors: Dominant Tactics and Jealous Tactics, along the lines of the original study. The reliability of the scale was good. With regard to convergent validity, positive and significant correlations were observed with the modified version of the Conflicts Tactics Scale (M-CTS; Neidig, 1986), which measures physical and verbal violence in dating relationships. With regard to known groups validity, we observed significant differences in dominant and jealous tactics as a function of age and gender, in the expected direction. This scale is a reliable and valid instrument to assess dominant and jealous tactics in dating relationships of youth and adolescents in Spain.